Study of charge transfer process in system of «hemoglobin-electrode» at level of individual molecules - N. A. Davletkildeev; D. V. Sokolov; E. A. Zimbovich; E. Yu. Mosur; I. A. Lobov (Омский научный вестник)
The process of electron transfer through an individual hemoglobin molecule (Hb) has been studied by conductive atomic force microscopy. It is shown that the current through the Hb molecule arises at applied force equal 45 nN. According to estimates, the height of the deformed molecule is 4,5 nm. Based on the analysis of the experimental I-V characteristic of the probe/Hb/substrate contact using of the non-resonant tunneling transport model, the parameters of tunnel electron transport through the individual Hb molecule are determined.